2019
DOI: 10.1144/jgs2019-018
|View full text |Cite
|
Sign up to set email alerts
|

West Gondwana orogenies and Pangaea break-up: thermotectonic effects on the southernmost Mantiqueira Province, Brazil

Abstract: The final inverse model of each sample can be found below. Final models were run with all data available for the sample, as indicated in each figure. Black line represents the expected model, that is, a weighted mean model, where the weighting is provided by the posterior probability for each model. The expected model is the one displayed in figures 6 and 7 of the paper. Confidence intervals represent a 95% probability range. Black dots placed according the AFT central age of the sample. For further informatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 117 publications
2
6
0
Order By: Relevance
“…Our data combined with previous studies (e.g. Amaral-Santos et al, 2019;Cogné et al, 2011;Hueck et al, 2019;Japsen et al, 2012;Jelinek et al, 2014;Krob et al, 2019;Oliveira et al, 2016;Machado et al, 2019;Van Ranst et al, 2020a) show a widespread erosional denudation during the Late Cretaceous to Paleocene that is strongly imprinted in some of the segments of the Brazilian Atlantic margin, such as the Borborema Province (e.g. Morais Neto et al, 2009) and Mantiqueira Province (e.g.…”
Section: Late Cretaceous -Paleocenesupporting
confidence: 84%
See 1 more Smart Citation
“…Our data combined with previous studies (e.g. Amaral-Santos et al, 2019;Cogné et al, 2011;Hueck et al, 2019;Japsen et al, 2012;Jelinek et al, 2014;Krob et al, 2019;Oliveira et al, 2016;Machado et al, 2019;Van Ranst et al, 2020a) show a widespread erosional denudation during the Late Cretaceous to Paleocene that is strongly imprinted in some of the segments of the Brazilian Atlantic margin, such as the Borborema Province (e.g. Morais Neto et al, 2009) and Mantiqueira Province (e.g.…”
Section: Late Cretaceous -Paleocenesupporting
confidence: 84%
“…6) affected at least the SFC (Jelinek et al, 2014;Japsen et al, 2012 at the craton's continental margin) and Brasília Orogen (Fonseca et al, 2020). In the Matiqueira Province (Borba et al, 2002(Borba et al, , 2003Hueck et al, 2019;Machado et al, 2019;Oliveira et al, 2016;Ribeiro et al, 2005;Souza et al, 2014), Amazonian Craton (Harman et al, 1998) and ancient West Gondwana basement terrains in Africa (Kasanzu, 2017;Kasanzu et al, 2016), a Paleozoic cooling is also reported. The majority of the previous works argued for a far-field mechanism inducing widespread erosion and exhumation of the West Gondwana basement during this time (e.g.…”
Section: Paleozoicmentioning
confidence: 96%
“…Gondwanic cycle) and which has been also reported further south in Argentina and north in southernmost Brazil (Borba et al 2002(Borba et al , 2003Oliveira et al 2016;Kollenz et al 2017;Machado et al 2019). They suggest that the late Mesozoic reheating phase is associated to the Paraná-Etendeka LIP, which lava flows would have buried the UYS and caused an increase in the bedrock temperature.…”
Section: Results Of Previous Thermochronometry Studies In Uruguaymentioning
confidence: 86%
“…The onset of this cooling phase is correlated to the Gondwanic cycle, characterized by subduction of the Panthalassa Ocean and accretion of exotic terranes on the SW margin of Gondwana (Fig 1) (Scotese et al 1999;Milani & Wit 2008). Intraplate stress transmission linked to these collisions reactivated basement structures below the Paraná Basin and surrounding areas (Milani & Wit 2008), with deformation and exhumation inferred from NE Argentina to southern Brazil until the Triassic (Zambrano & Urien 1970;Zerfass et al 2004;Pankhurst et al 2006;Oliveira et al 2016;Machado et al 2019). Therefore, the onset of this major cooling phase in the UYS is likely related to far field propagation stress and deformation caused by the Gondwanic cycle.…”
Section: Thermochronometry Agesmentioning
confidence: 99%
See 1 more Smart Citation